Madrasah Culture: Implementation of Religious Character Education in Madrasah Ibtidaiyah - Sari, Putri Sekar; Sumedi, Sumedi (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
Character education has become a must in the world of education, because character education not only makes students smart in thinking but also can build character and manners in everyday life. The purpose of this study is to describe the implementation of religious character education through madrasah culture. This research was conducted at MI Annasirin Al Islami in the odd semester of TA. 2023/2024. The sampling technique used purposive sampling with the research subject of grade 2 students totaling 20 students consisting of 12 male students and 8 female students. This type of research is descriptive qualitative, with data collection through interviews, observation and documentation. The data collected was analyzed with an interactive data analysis model which includes the process of condensing data, presenting data, and finally concluding the results. Then the researchers conducted a verification process with data triangulation to maintain data validity. The results showed that the implementation of religious character education through madrasah culture was carried out through religious activities, routine activities, exemplary and habituation. Through the implementation of these activities, it is hoped that it can provide provisions and indications for the personality of students to become a generation that has good morals, adab, spirituality and behavior.